Microscopic distribution of taxanes in freeze-fixed stems of Taxus cuspidata - Gong, Qinyue; Aoki, Dan; Yoshida, Masato; Fukushima, Kazuhiko (Frontiers in Chemistry, 2024)
Introduction Taxus species contain the anticancer alkaloid paclitaxel, as well as other taxanes similar in structure and potentially in effect to paclitaxel. Tissue-specific distribution patterns and seasonal variations of taxanes in some Taxus species have been reported; however, it is still under-presented for the taxanes in Taxus cuspidata. Methods The radial distributions of eight taxanes in the transverse surface of freeze-fixed T. cuspidata stems from the late summer and the spring seasons were investigated by cryo-time-of-flight secondary ion mass spectrometry and scanning electron microscopy (cryo-TOF-SIMS/SEM) visualization and liquid chromatography-mass spectrometry (LC-MS) quantitative analysis. By optical microscopic observation, seasonal differences in the amounts and distribution patterns of target taxanes were further characterized in specific tissues. Results and Discussion The overall amount of taxanes was higher in the late summer than in the spring. Also, taxanes’ radial distribution was generally found at higher concentration in the phloem, the cambium and lower level in the periderm, the latest-forming xylem, with different taxanes showing several patterns with distinction between seasons, which were considered related to seasonal plant physiological behaviors. In addition, the distribution of baccatin III (BAC) was investigated at the cellular level, which was regarded in specific cells suggesting its transport in the radial and axial directions in the T. cuspidata stem. Characterizing the microscopic distribution of taxanes in the T. cuspidata stem is expected to play a role in the further study of their biosynthesis and in planta behaviors.